Immunoparesis defined by heavy+light chain suppression is a novel marker of long‐term outcomes in cardiac AL amyloidosis. (8th October 2017) - Sachchithanantham, Sajitha; Berlanga, Oscar; Alvi, Azra; Mahmood, Shameem A.; Lachmann, Helen J.; Gillmore, Julian D.; Hawkins, Philip N.; Harding, Stephen; Wechalekar, Ashutosh D.
Summary: Cardiac involvement and presenting dFLC (difference between involved and uninvolved free light chains) are independent predictors of outcome in systemic AL amyloidosis. These markers have limited prognostic utility in patients surviving the initial months following diagnosis. Here we assessed immunoparesis, as determined by novel heavy+light chain (HLC) immunoassays, as a prognostic marker for survival in AL amyloidosis. HLC measurements identified immunoparesis of at least one immunoglobulin (Ig) isotype in 145 (85%) patients; and severe immunoparesis (≥2 Ig isotypes suppressed by >50% below normal levels) in 29 (17%) patients. Median overall survival (OS) on intention to treat (ITT) analysis was 26·2 months. In the ITT cohort, dFLC >180 mg/l was associated with shorter OS ( P = 0·05); whereas HLC immunoparesis was not prognostic. On a landmark analysis of 127 patients alive at 6 months, presenting dFLC was not prognostic for OS ( P = 0·33) and severe HLC immunoparesis trended towards poorer survival (20·2 vs. 42·8 months; P = 0·09). In the subset of patients with cardiac involvement, severe HLC immunoparesis conferred very poor outcome (median OS 8·8 vs. 29·9 months, P = 0·007). In conclusion, severe HLC immunoparesis is an independent marker of long‐term poor prognosis in AL patients with cardiac involvement. The pathophysiological significance of this observation needs further study.